A comparison of oral bacteriome isolated from periodontal pockets of participants with or without diabetes mellitus in Uganda: a case control study - Kiryowa, Haruna Muhmood; Buwembo, William; Munabi, Ian Guyton; Mwaka, Erisa Sabakaki; Rwenyonyi, Charles Mugisha; Kaddumukasa, Mark; Kiguli, Sarah (BioMed Central Ltd, 2024)
Abstract Objective Diabetes mellitus predisposes patients to increased incidence and severe forms of periodontal disease. Currently, information on the bacterial diversity of patients with diabetes mellitus and periodontitis in Uganda is scanty. This study set out to describe the bacteria associated with periodontitis in patients with diabetes mellitus in Uganda, as part of a larger study describing the association between periodontal disease and diabetes mellitus. Results This was a case control involving 45 samples of gingival crevicular fluid collected from participants with periodontitis, the cases being 26 participants with diabetes mellitus and controls 19 participants without diabetes mellitus. Sequencing using the 16s Oxford nanopore long read protocol was followed by a bioinformatics analysis pipeline for alpha and beta diversity indices in the two groups. Multivariate tests were done to determine the differences in the bacterial composition in the two groups. Of the 739 Operational Taxonomic Units and 500 phyla identified, 37.9% (280/739) were from participants with diabetes mellitus. Analysis of beta diversity revealed a dissimilarity between the two study groups (CAP score=0) with a significant association noted between periodontitis and the subgingival bacteria (P=0.001). Diabetes mellitus reduced the quantity and altered the composition of the subgingival microbiome in the study participants. Keywords Diabetes mellitus, Microbiome, OTUs, Periodontal pockets and periodontitis
Keywords: Diabetes mellitus, Microbiome, OTUs, Periodontal pockets and periodontitis